Non-magnetized mixed convective viscous flow submerged in titanium oxide and aluminum titanium oxide hybrid nanoparticles towards a surface of cylinder - Haq, Fazal; Khan, M. Ijaz; Chu, Yu-Ming; Khan, Niaz B.; Kadry, Seifedine (International communications in heat and mass transfer, 2021)
Hybrid nanofluids are novel fluids created by suspending two or more dissimilar nano sized particles in base fluids. Thermal conductivity of hybrid nanofluids is more than nanofluids. Now a day, due to high thermal conductivity and applications in engineering and industry, hybrid nanofluids have become attractive area of research for scientist and researchers. The main objective of current communication is to study the stagnation point flow and heat transfer in viscous hybrid nanofluid towards a stretched cylinder. Flow characteristics are examined under the effect of magnetic field and mixed convention. Furthermore, energy communication is constructed considering thermal radiation, uniform heat source and viscous dissipation. The obtained governing dimensional model is transformed into ordinary ones using suitable transformations. ND-solve code is used to tackle the ordinary differential equations. Results are discussed and compared subject to nanofluid and hybrid nanofluid and plotted graphically. Moreover, Nusselt number and skin friction coefficient are studied numerically. Key outcomes are highlighted at the end.